EFFECT OF ROTIFERS (Branchionus plicatilis) REPLACEMENT WITH PREDIGESTED ARTIFICIAL FEED ON SURVIVAL AND LARVAE DEVELOPMENT OF BLUE SWIMMING CRAB (Portunus pelagicus) - Sudaryono, Agung; Alik T, Widyawati; Aslamyah, Siti; Fujaya, Yushinta (Indonesian Aquaculture Society (MAI), 2015)
One of the problems faced in blue swimming crab hatchery business is the reliance on the use of natural feed. This research aimed to study the effect of rotifer feed replacement by predigested artificial feed on survival rates, growth rates of the larval stages and to determine the best feeding period of predigest artificial feed 100% to replace rotifers. The study was conducted in May-June 2015 in a household scale hatchery location at Bojo Village, Mallusettasi District, Kabupaten of Barru. There were five replacements of rotifers by predigest artificial feed namely: A. Control (feeding with rotifer up to stadia zoea 4), B (feeding with rotifer up to stadia zoea 3), C (feeding with rotifer up to stadia zoea 2), D (feeding with rotifer only at stadia zoea 1), E (No feeding with rotifer). Predigest artificial feeds were fed for a rearing period of larvae in all treatments. The results showed that the survival of the blue crabs larvae that did not consume rotifers as a feed source were significantly lower than the crab larvae consuming rotifers. The larvae with no feeding rotifer survived only at stadia zoea-2 while those feeding with rotifers survived until zoea-4. The rate of stadia changes did not differ among treatments getting rotifers. Use of predigest artificial feed on crab hatchery can be an alternative to rotifers in the future. Feeding predigest 100% can be started at stadia zoea-2. Key words: blue swimming crab, Portunus pelagicus, larvae, rotifers, predigest artificial feed.